SYSTEMATIC LITERATURE REVIEW (SLR): Hakikat Implementasi ‎Kurikulum di Madrasah Dalam Perspektif Filsafat Pendidikan Islam ‎ - Hamdan, Muhamad (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The aim of this research is to describe the curriculum concept, function, approach, development and implementation of the curriculum. The methodology in this research is a systematic review research sourced from published journals from 2018 to 2022. The research sample was in the form of published journals on Google School and Science Direct as many as 7 journals about the curriculum. The result of this research is that the curriculum holds a very important position, the criteria become a standard reference for the learning process carried out in an education system. Implementation of this curriculum aims to standardize implementation. Curriculum development must truly be carried out with good educational goals. Curriculum development should not become a means for politics for a few people to seek certain popularity. Appropriate steps have a separate section regarding the development of educational curricula both in public schools and madrasah schools. In terms of curriculum implementation, both public schools and madrasahs should follow the reference standards that have been established.